Implementasi Aplikasi digitalisasi Produk UMKM dengan E-Katalog dan GIS secara terpadu untuk Pemetaan dan optimasi penjualan - Agustinus Santoso; Ivan Permana; Edwin Zusrony; Maya Utami Dewi (STEKOM PRESS, 2022)
The behavior of changing the use of technology for business actors is very rapid. Information of system is form of data that has been processed through a certain model into information that can be used by the recipient in making decisions. Some MSME actors with a Data List of product images and detailed information on their products to be marketed to customers using laminated paper. Marketing information using the Website implements CMS with E-Catalog as an alternative solution. Reader and Viewers can view the Catalog privately or together. The treatment of the Plugin model with the CMS that has been embedded on the website is reliable because it is online. Several list images are displayed on WhatsApp Status and social media to introduce products to the public with the aim of increasing sales volume and selling in the market. This is an obstacle if one day people need pictures but do not have complete detailed information. High purchasing power is expected to be created from the spread of E-Catalog regarding products from MSMEs that have been installed on the E-Catalog website. Websites with online CMS can be opened on any device by requiring an internet connection, making it easier for marketing and complete information for consumers, customers and MSME business players.